EMaaS: Cloud-Based Energy Management Service for Distributed Renewable Energy Integration - Yu-Wen Chen; Chang, J. Morris (IEEE transactions on smart grid, 2015)
The increasing penetration of renewable energy has become a critical issue in recent years. The future power system is foreseen to depend on distributed energy resource (DER) excessively for continuous load support. Yet, DER providers are also facing limited choices in their produced renewable energy. Massive information and complicated cooperation emerging from involvers intensify issues in terms of efficiency, reliability, and scalability. In this paper, a cloud-based framework is proposed to provide a customer-oriented energy management as a service (EMaaS) for green communities, which are formed as virtual retail electricity providers (REPs) by involved DERs providers. It can be adopted by existing REPs or utilities. For each green community, the multiperiod global cost is minimized to promote renewable energy, and renewable energy consumption is stabilized to enhance integration. A solvable linear programming model is formulated for EMaaS. The case studies results reveal the proposed EMaaS retains satisfactory performances.